ยุทธศาสตร์การพัฒนาศักยภาพของบุคลากรด้านการพัฒนางาน ประจำสู่งานวิจัย : กรณีศึกษาแขนงข้อมูลข่าวสารทรัพยากรธรรมชาติ แขวงคำม่วน สาธารณรัฐประชาธิปไตยประชาชนลาว - ลัดสะจัก, พันทะนาม (Journal of Graduate School Sakon Nakhon Rajabhat University, 2017)
ยุทธศาสตร์การพัฒนาศักยภาพของบุคลากรด้านการพัฒนางานประจำสู่งานวิจัย : กรณีศึกษาแขนงข้อมูลข่าวสารทรัพยากรธรรมชาติ แขวงคำม่วน สาธารณรัฐประชาธิปไตยประชาชนลาว STRATEGY TO DEVELOP STAFF MEMBERS’ COMPETENCY IN ESTABISHMENT OF ROUTINE–TO-RESEARCH : THE CASE STUDY OF THE NATURAL RESOURCES INFORMATION BRANCH KHAMMOUANE PROVINCE, LAO PEOPLE’S DEMOCRATIC REPUBLIC บทคัดย่อ การวิจัยครั้งนี้มีจุดมุ่งหมายเพื่อ 1) ศึกษาสภาพปัจจุบันและความต้องการพัฒนาศักยภาพด้านการพัฒนางานประจำสู่งานวิจัย: กรณีศึกษาแขนงข้อมูลข่าวสารทรัพยากรธรรมชาติ แขวงคำม่วน สาธารณรัฐประชาธิปไตยประชาชนลาว 2) สร้างยุทธศาสตร์การพัฒนาศักยภาพของบุคลากรด้านการพัฒนางานประจำสู่งานวิจัย และ 3) ศึกษาผลการทดลองใช้ยุทธศาสตร์การพัฒนาศักยภาพของบุคลากรด้านการพัฒนางานประจำสู่งานวิจัย กลุ่มเป้าหมายเป็นบุคลากรแขนงข้อมูลข่าวสารทรัพยากรธรรมชาติ จำนวน 11 คน เครื่องมือที่ใช้ในการวิจัยได้แก่ แบบสัมภาษณ์ชนิดแบบมีโครงสร้าง แบบทดสอบความรู้ และแบบวัดเจตคติต่อการพัฒนางานประจำสู่งานวิจัย สถิติที่ใช้ในการวิเคราะห์ข้อมูล ได้แก่ ค่าร้อยละ ค่าเฉลี่ย และส่วนเบี่ยงเบนมาตรฐาน ผลการวิจัยพบว่า 1. สภาพปัจจุบันและความต้องการพัฒนาศักยภาพด้านการพัฒนางานประจำสู่งานวิจัย (R to R) ของบุคลากรจากผลการประเมินตนเองอยู่ในระดับน้อย ( = 1.27, S.D. = 0.46) และความต้องการพัฒนาตนเองของบุคลากรในเรื่องดังกล่าวอยู่ในระดับมากที่สุด ( = 4.34, S.D. = 0.77) โดยมีแนวทางการพัฒนาที่ต้องการมากที่สุด ได้แก่ ต้องการให้มีการจัดอบรมให้ความรู้ โดยใช้วิทยากรที่เชี่ยวชาญ ระหว่างอบรมให้มีการฝึกทักษะด้านต่างๆ ที่เกี่ยวข้องและเมื่อเสร็จสิ้นการอบรมได้มีการลงมือปฏิบัติ การทำวิจัยเพื่อพัฒนางานประจำจริง และให้มีการศึกษาดูงานหน่วยงานที่ประสบความสำเร็จในการทำวิจัยเพื่อพัฒนางานประจำ 2. ยุทธศาสตร์การพัฒนาศักยภาพของบุคลากรด้านการพัฒนางานประจำสู่งานวิจัยที่สร้างขึ้น มีเป้าหมายสำคัญเพื่อพัฒนาความรู้ ความเข้าใจและความสามารถในการเขียนข้อเสนอโครงการวิจัยเกี่ยวกับการพัฒนางานประจำสู่งานวิจัย รวมทั้งเสริมสร้างเจตคติที่ดีต่อการทำวิจัยเพื่อพัฒนางานประจำให้กับบุคลากรแขนงข้อมูลข่าวสารทรัพยากรธรรมชาติ แขวงคำม่วน สาธารณรัฐประชาธิปไตยประชาชนลาว กิจกรรมสำหรับยุทธศาสตร์มี 3 กิจกรรม ได้แก่ การอบรมพัฒนาความรู้ ความเข้าใจเกี่ยวกับการพัฒนางานประจำสู่งานวิจัย การศึกษาดูงานหน่วยงานที่ประสบผลสำเร็จและการปฏิบัติการเขียนข้อเสนอโครงการวิจัย 3. ผลการทดลองใช้ยุทธศาสตร์ พบว่า 3.1 ความรู้ ความเข้าใจเกี่ยวกับการพัฒนางานประจำสู่งานวิจัยของบุคลากรหลังการใช้ยุทธศาสตร์เท่ากับร้อยละ 80.22 ซึ่งมากกว่าก่อนการใช้ยุทธศาสตร์ที่คะแนนเฉลี่ยเท่ากับร้อยละ 38.46 3.2 เจตคติเกี่ยวกับการพัฒนางานประจำสู่งานวิจัยของบุคลากรหลังการใช้ยุทธศาสตร์ดีกว่าก่อนการใช้ยุทธศาสตร์ 3.3 หลังการใช้ยุทธศาสตร์บุคลากรทุกคนร่วมการทำโครงการวิจัยเรื่องการเสริมสร้างศักยภาพในการออกโฉนดที่ดินของแขนงข้อมูลข่าวสารทรัพยากรธรรมชาติ แขวงคำม่วน สาธารณรัฐประชาธิปไตยประชาชนลาว พบว่า หลังอบรมสูงกว่าก่อนอบรม ABSTRACT The purposes of this study were: 1) to investigate the current state and need of developing staff members’ competency in establishment of routine-to-research by having a case study in the National Resources Information Branch, Khammouane province, Lao People’s Democratic Republic, 2) to create a strategy to develop staff members’ competency in establishment of routine-to-research, and 3) to inquire into the results of implementing the strategy to develop staff members’ competency in establishment of routine-to-research. The target group was 11 staff members of the National Resources Information Branch. The instruments used in study were: a structured interview guide, a test of knowledge, and a form for measuring the attitude towards the establishment of routine-to-research. Statistics used in data analysis were percentage, mean and standard deviation. Findings of the study were as follows: 1. The current state of staff members’ knowledge about the establishment of routine-to-research through self-assessment was found at low level ( = 1.27, S.D. = 0.46) and the need of staff members’ self-development in this matter was at highest level ( = 4.34, S.D. = 0.77). The most needed way to develop was a training of knowledge through expert lecturers. Related various skills were practiced during the training and the real action of doing research to develop routine work was offered at the end of training. A study trip to the work units successful in doing research for developing the routine work was made. 2. The created strategy to develop staff members’ competency in establishment of routine-to-research had significant targets to develop knowledge, understanding and capability to write a research proposal of developing routine to research, and to strengthen positive attitude of staff members of the Natural Resources Information Branch, Khammouane province, Lao People’s Democratic Republic towards doing research for developing routine work. The strategy was composed of 3 activities: training for development of knowledge and understanding about routine to research establishment; a study trip to the successful work units; and practicing in writing a research proposal. 3. The results of experiment in implementing the strategy showed as follows: 3.1 Staff members’ knowledge and undestanding about routine-to-research after implementing the strategy was equal to 80.22%which was higher than that before implementing it with a percentage of 38.46 3.2 Staff members’ attitude toward establishment of routine-to-research after implementing the strategy was better than that before the treatment. 3.3 After the strategy implementation, every staff member participated in doing a research project entitled‘ Strengthening the Competency in Issuing Title Deeds of the Natural Resources Information Branch, Khammouane Province, Lao PDR.